Hubungan Lingkungan Belajar Klinik dengan Tingkat Kecemasan Mahasiswa pada Program Pendidikan Ners: The Relationship Between Clinical Learning Environment and Anxiety Levels in Nursing Students on the Nursing Education Program - Nelwati; Triyana Harlia Putri; Atih Rahayuningsih (Fakultas Keperawatan Universitas Andalas, 2012)
Clinical learning environment is the vehicle of clinical learning. However, a less supportive clinical environment may trigger anxiety in students while learning. The purpose of this study was to determine the correlation between clinical learning environment relationships and levels of anxiety in student nurses in the Nursing Science Study Program, Faculty of Medicine, Andalas University, 2011. This research used a cross-sectional approach with 69 students as respondents. The data was collected by applying two questionnaires, SECEE and DASS. The study showed that 49% of student nurses have a bad clinical learning environment, and 56.5% of student nurses have high levels of anxiety. There was a significant association between the clinical learning environment and levels of anxiety, with Spearman rank analysis p-value=0.000 and r=-0.769. Application of a mentorship method is needed in any room while having clinical learning in order to increase trust, self-dignity, confidence, and competence achievement of students.